Applying Systems Thinking via Systemigrams™ for Defining the Body of K nowledge and Curriculum to Advance Systems Engineering (BKCASE) Projec t - Squires, Alice; Pyster, Art; Sauser, Brian; Olwell, David; Enck, Stephanie; Gelosh, Don; Anthony, Jim (INCOSE International Symposium, 2010)
Systems thinking is commonly accepted as the backbone of a successful systems engineering approach. As such, the Body of Knowledge and Curri culum to Advance Systems Engineering (BKCASE) team chose to leverage a systems thinking based tool, called Systemitool, to describe our proj ect to the vast audience that would potentially become involved direct ly or indirectly in the success of the project. This paper describes t he process and steps used by the authors and the BKCASE team to develo p the project's systemic diagram, or Systemigram™, and the story behin d the project, the products, and the vision of the BKCASE project. The goal of the paper is to provide guidance so that readers can leverage the lessons learned from this effort to successfully develop their ow n project definitions and stories.